POLITICAL IMAGE AS A TOOL FOR STRATEGIC POSITIONING IN POST-PANDEMIC ELECTORAL CAMPAIGN - Maydanskyi, Ivan; Zienkin, Mykhailo (Public Management and Policy, 2025)
The article examines political image as a tool for strategic positioning in post-pandemic electoral campaigns. The main focus is on analyzing the impact of crisis conditions, media communications, and digital platforms on the formation and effectiveness of political leaders’ images in Europe and North America. Research aim: to determine how political image influences citizens’ electoral preferences in the post-pandemic period, identify effective strategies for its formation, and assess the role of media and social networks in building voter trust and support. The study is based on a comprehensive approach that includes content analysis of public speeches and media materials of political leaders, comparative analysis of post-pandemic electoral campaigns, analysis of sociological data and approval ratings, case studies (using Donald Trump in the USA and Angela Merkel’s government in Germany as examples), and synthesis of data from various sources. The study revealed that political image becomes a key factor for campaign success under crisis conditions. Candidates who demonstrated competence, transparency, and effective crisis management received consistently positive audience perception and increased approval ratings. Active use of media and digital platforms enhances the influence of image on public opinion, builds trust, and legitimizes political authority. Comparative analysis of campaigns in different countries confirmed the universality of these strategies in Europe and North America. In the post-pandemic period, political image is a critical tool for strategic positioning, shaping voter behavior and determining electoral outcomes. Its effective construction and management are an integral part of modern political management. The study confirms that integrating digital technologies and media strategies into image formation becomes a key factor for candidates’ competitive advantage. Furthermore, the results can be used to develop practical recommendations for improving the effectiveness of electoral campaigns in various political contexts.